Pengembangan Model Pengenalan Air Cabang Renang Tingkat Sekolah Dasar - Yoga Septia; Ade Jubaedi; Suranto Suranto (JUPE (Jurnal Penjaskesrek), 2018)
The purpose of this research are as follows: (1) to find out the need of development of swimming pool introduction model at primary school level for swimming ability and (2) to know how to develop water swimming pool introduction model at elementary school level. The research method used is research and development (R D) with Borg and Gall development model. Data analysis using t-test to know the effectiveness of product development of water recognition model, that is the result of expert material assessment get very good result. The population in this study amounted to 65 students and the sample in this study were 32 students. Based on the result of the research, it can be concluded that: (1) there is a need to develop a swimming pool introduction model at the elementary level for swimming skills (2) there is a way to develop a swimming pool introduction model at elementary school level.Tujuan penelitian ini sebagai berikut: (1) untuk mengetahui kebutuhan pengembangan model pengenalan air cabang renang pada tingkatan sekolah dasar untuk keperluan kemampuan berenang dan (2) untuk mengetahui bagaimana cara mengembangkan model pengenalan air cabang renang pada tingkatan sekolah dasar. Metode penelitian yang digunakan ialah penelitian dan pengembangan (RD) dengan model pengembangan Borg and Gall. Analisis data meggunakan t-test untuk mengetahui efektivitas produk pengembangan model pengenalan air, yaitu hasil penilaian ahli materi memperoleh hasil sangat baik. Populasi dalam penelitian ini berjumlah 65 siswa dan sample dalam penelitian ini adalah 32 siswa. Berdasarkan hasil penelitian dapat disimpulkan: (1) ada kebutuhan pengembangan model pengenalan aircabang renang pada tingkatan sekolah dasar untuk keperluan kemampuan berenang (2) ada cara mengembangkan model pengenalan air cabang renang pada tingkatan sekolah dasar.Kata kunci: pengenalan air, renang, sekolah dasar